2008
DOI: 10.1093/jac/dkn508
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability for behaviour change in the fight against antibiotic resistance: a social marketing framework

Abstract: Antibiotic resistance is one of today's most urgent public health problems, threatening to undermine the effectiveness of infectious disease treatment in every country of the world. Specific individual behaviours such as not taking the entire antibiotic regimen and skipping doses contribute to resistance development as does the taking of antibiotics for colds and other illnesses that antibiotics cannot treat. Antibiotic resistance is as much a societal problem as it is an individual one; if mass behaviour chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 50 publications
0
51
0
4
Order By: Relevance
“…ABR is as much a society problem as it is an individual one, [20] this paper demonstrates that collective action can be successful if interventions are designed correctly. The leading systematic review in this area concluded that multifaceted interventions are more successful in changing antibiotic prescribing practices [11] and that interactive meetings and audit reports can influence GP prescribing behaviors.…”
Section: Discussionmentioning
confidence: 84%
“…ABR is as much a society problem as it is an individual one, [20] this paper demonstrates that collective action can be successful if interventions are designed correctly. The leading systematic review in this area concluded that multifaceted interventions are more successful in changing antibiotic prescribing practices [11] and that interactive meetings and audit reports can influence GP prescribing behaviors.…”
Section: Discussionmentioning
confidence: 84%
“…reuteri CH1 had the lowest resistance (23.3%) towards the test antibiotics, survived 3% physiological bile, simulated pH (3.0-9.5), and exhibited significant spectrum of inhibitory activities against 7 reference strains and 12 selected gastroenteritic strains from children (Table 3). [2] 100.0 100.0 100.0 Cotrimoxazole [4] 30.6 43.8 70.0 Erythromycin [2] 81.8 100.0 100.0 Metronidazole [8] 77.1 84.4 86.1 NANT [5] 100.0 100.0 100.0 NANT = non antibiotic anti-gastroenteritic medications …”
Section: Resultsmentioning
confidence: 99%
“…Gastroenteritis is still a major worldwide problem among infants and children, and one of the principal causes of infantile sickness and death in more than 85% of the world population 1. Although antibiotic therapy has been the mainstay in the treatment of diarrhoeal cases, the onset of drug resistance threatens virtually all classes of antibacterial agents 2 and though the magnitude of the problem may vary from place to place, the problem of antibiotic resistance is quite alarming in tropical developing countries. Several workers in this country and elsewhere have also highlighted the problems of antibiotic resistance 3,4. An alternative therapeutic approach, based on oral administration of live bacteria has therefore been under active consideration 5, 6, 7, 8. More than 95% of infants in Africa are currently breastfed but feeding practices are often inadequate and the importance of breast milk as a food resource in African countries is also not generally recognised 9. Although it is important that babies are given extra food, as well as breast milk, at the right age and in sufficient amounts, to enable them grow and stay healthy, new studies on breastfeeding have also discovered or confirmed the benefits of breastfeeding to mother and child 10 , while human milk has also been found to contain several antiviral and antibacterial factors 11. In a study with data from India, Peru and Ghana on hospitalisation for diarrhoeal and respiratory illness 12, non-breastfed infants had a higher risk of all causes of hospitalisation when compared to infants who had been predominantly breastfed and also had a higher diarrhoea-specific hospitalisation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, relying on principles of social marketing, which mirrors an approach to behavior change used by commercial marketers, provides the medical community with a multi-pronged approach that goes beyond simple messaging and offers guidance on how to restructure the environment in which health-related decisions get made. 2 We also need to look beyond traditional channels of communication and examine how social media tools such as Facebook, Twitter, and blogging can be integrated into a comprehensive strategy for change. 7 I strongly believe we will be able to claim victory in the long run if we take a careful look at the barriers that lie ahead and construct effective approaches to overcome the obstacles.…”
mentioning
confidence: 99%